FINANCIAL FEASIBILITY OF â€œSALAK PONDOH CRISPYâ€ INDUSTRY - Hidayat, Nur; Purwaningsih, Heni; Kaliky, Rahima (Agros Journal of Agriculture Science, 2005)
â€œSalak pondohâ€ (Salacca edulis reinw) representing typical commodity in Yogyakarta and represent one among superior commodity at Sleman regency which its growth started by have sufficiently long and get enough the government attention, where infrastructure for the fluency current of input and output have been made available inclusive of its marketing institute. Greater harvest price salak pondoh very low so profit farmer advantage also. To overcome the mentioned of there were some farmer salak pondoh that is with the diversification product and one of them is crispy processing. To see To see what the effort farmerâ€™s profit or do not hence have been done by research. This research aim to know the eligibility financial of effort industry of processing kripik barks the pondoh. The research was conducted in Bangunkerto village and Donokerto village of District Turi and Lumbungrejo village, Tempel District Sleman Regency on November until December 2004. Research method used by method the survey, data type collected covers the data of primary and secondary. Primary data obtained from interview with the farmer bark the pondoh use the questionnaire; secondary data is secondary obtained from Biro Pusat Statistik DIY and other institution which is related to this research. Intake sample conducted by purposive and responder determined by counted 60 people. The data mustered tabulation was analyzed descriptively and to analysis technical financial feasibility by NPV, IRR, B/C and Payback Period. Research result indicated that industrial Investment crispy bark of pondoh processing by financial is competent for developed that shown from positive value NPV, higher IRR Estimation from storey; level of rate of interest actual, and B/C ratio > 1